2021
DOI: 10.1002/smll.202100832
|View full text |Cite
|
Sign up to set email alerts
|

Cr‐Doped CoP Nanorod Arrays as High‐Performance Hydrogen Evolution Reaction Catalysts at High Current Density

Abstract: Developing highly efficient, low‐cost electrocatalysts with long‐time stability at high current density working conditions for hydrogen evolution reaction (HER) remains a great challenge for the large‐scale commercialization of hydrogen production from water electrolysis. Herein, the Cr‐doped CoP nanorod arrays on carbon cloth (Cr‐CoP‐NR/CC) is reported as high performance HER catalysts with overpotentials of 38 and 209 mV at the HER current densities of 10 and 500 mA cm−2, respectively, outperforming the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 49 publications
0
45
0
Order By: Relevance
“…Indeed, catalyst surface (e.g., composition, structure, defect, strain, doping), heterostructure with interfacial interaction, and surface spectator, etc., all influence the surface chemistry of the catalysts and some of them have been used to tune HCD performance. [93][94][95][96][97] Engineering the surface chemistry of catalysts is a basis to achieve high performance at HCDs.…”
Section: Surface Chemistrymentioning
confidence: 99%
“…Indeed, catalyst surface (e.g., composition, structure, defect, strain, doping), heterostructure with interfacial interaction, and surface spectator, etc., all influence the surface chemistry of the catalysts and some of them have been used to tune HCD performance. [93][94][95][96][97] Engineering the surface chemistry of catalysts is a basis to achieve high performance at HCDs.…”
Section: Surface Chemistrymentioning
confidence: 99%
“…To interpret the HER stability of Co 2 P&CoP@N−C NAs, the XPS spectra of Co 2 P&CoP@N− C NAs after the HER process are shown in Figure S24. The disappearance of the Co 2p peaks at 778.4 and 793.3 eV is probably due to the oxidation of Co species during the long-term durability measurement, 41,42 while the P 2p peaks of Co 2 P&CoP@N−C NAs were partially reserved after the stability test. Combining the above analysis, the stability of Co 2 P&CoP@N−C NAs may be related to the metal phosphide surface, protected by the N−C support.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Nanomaterials as catalytic materials have important application value in energy conversion and storage devices. [221][222][223][224][225][226][227][228][229][230][231][232][233][234][235] There are many classification methods of nanomaterials, according to their structures can be divided into: 0D, [236][237][238][239] 1D, [240][241][242] 2D, [243,244] and 3D nanomaterials. [245][246][247] For example, Liu et al [248] reported the 3D niconitrides nanoparticles/NiCo 2 O 4 nanoflakes/graphite fibers (NiCo-nitrides/NiCo 2 O 4 /GF), which was designed and fabricated by assembling nitride-oxides hetero-nanostructures onto graphite fibers via a simple electrochemical deposition and subsequent in situ nitridation (Figure 9a).…”
Section: Nanostructuringmentioning
confidence: 99%
“…Nanomaterials as catalytic materials have important application value in energy conversion and storage devices. [ 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 ] There are many classification methods of nanomaterials, according to their structures can be divided into: 0D, [ 236 , 237 , 238 , 239 ] 1D, [ 240 , 241 , 242 ] 2D, [ 243 , 244 ] and 3D nanomaterials. [ 245 , 246 , 247 ] For example, Liu et al.…”
Section: Strategies To Improve Her Electrocatalystsmentioning
confidence: 99%